Типологический принцип Бодуэна и верификация одной лингвистической теории - Мартынов, Виктор Владимирович (Kalbotyra, 1997)
This article demonstrates the usage of а typological principle of Bauduin de Courtenay in accordance with the reconstruction of the I.Е. and Сommon Slavic vocalic system. Their proximity is being manifested in the existence of synharmoniс syllables with the change of Ci̭e > Ci̭o before а non-palatalized consonant. In the Proto-I.E. language it gave rise to the ablaut e/o, whereas in Сommon Slavic this leads to the mild correlations of consonants, not including the fасt that the besides the syllable structure Со appeared also Ci̭o.